Arguing for the development of critical thinking skills amongst learners in the Zimbabwe education system - Ndlovu, Emily; Mangwaya, Ezron (2016)
The value of critical thinking skills to specific human activities and processes and to human life in general is unquestionable. Indeed, it may be difficult to imagine much meaningful existence without the aid of critical thinking skills. It is therefore, surprising that there is an unexplainable silence in the entire educational system in Zimbabwe regarding critical thinking skills. This paper seeks to explore the meaning and uses of critical thinking, thereby exposing its relevance to educational practice, both for the benefit of learners during their learning and in their life after school. The paper argues that failure to introduce learners to the skills of critical thinking and to incorporate critical thinking into the teaching/learning processes in schools and colleges is, in many ways, a great disservice to the students and to the Zimbabwean society as a whole. It urges concerted efforts to be instituted to introduce the teaching of critical thinking in both schools and colleges and encourages the employment of critical thinking skills in all facets of human life